2015
DOI: 10.1152/ajpregu.00083.2015
|View full text |Cite
|
Sign up to set email alerts
|

N-methyl-d-aspartate receptor coagonist d-serine suppresses intake of high-preference food

Abstract: d-Serine is abundant in the forebrain and physiologically important for modulating excitatory glutamatergic neurotransmission as a coagonist of synaptic N-methyl-d-aspartate (NMDA) receptor. NMDA signaling has been implicated in the control of food intake. However, the role of d-serine on appetite regulation is unknown. To clarify the effects of d-serine on appetite, we investigated the effect of oral d-serine ingestion on food intake in three different feeding paradigms (one-food access, two-food choice, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 82 publications
1
17
0
Order By: Relevance
“…We find that d -serine reduces HFD induced weight gain through a reduction in high fat food intake, which seems to depend on altered food preference. These data are in line with Sasaki et al., who described that d -serine suppresses intake of high preference food resulting in blunted weight gain [15] . However, in contrast to this previous study, in our experiments, mice exposed to HFD + d -serine resumed consuming HFD, albeit less than HFD control mice, which could be explained by differences in gut microbiota between and the expansion of obesogenic bacteria facilitating weight gain in our mouse facility.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We find that d -serine reduces HFD induced weight gain through a reduction in high fat food intake, which seems to depend on altered food preference. These data are in line with Sasaki et al., who described that d -serine suppresses intake of high preference food resulting in blunted weight gain [15] . However, in contrast to this previous study, in our experiments, mice exposed to HFD + d -serine resumed consuming HFD, albeit less than HFD control mice, which could be explained by differences in gut microbiota between and the expansion of obesogenic bacteria facilitating weight gain in our mouse facility.…”
Section: Discussionsupporting
confidence: 91%
“…One of those genes is serine racemase (SRR) [13] , which catalyzes the conversion from l -serine to d -serine, an important co-agonist of N-methyl- d -aspartate (NMDA) receptors. SRR function was recently suggested to regulate insulin secretion from pancreatic beta cells [3] , [14] , and chronic as well as acute supplementation of the SRR product d -serine reduced food intake and weight gain upon high fat diet (HFD) feeding in mice [15] , [16] . However, dysfunction of SRR, the d -serine degrading d -amino acid oxidase (DAO), and the main d -serine transporter alanine-serine-cysteine transporter 1 (Asc-1) are implicated in the development of schizophrenia, Alzheimer's disease, and depression [17] , [18] , [19] , [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%
“…This gene encodes mitogen-activated protein kinase kinase kinase 14, which is a serine/threonine protein-kinase. In mice, D-serine suppresses the intake of high-preference food[ 50 ]. Moreover, MAP3K14 gene knockout mice showed a reduction in the weight of the mammary fat pad.…”
Section: Discussionmentioning
confidence: 99%
“…The varying concentration of d -serine water was provided to mice fed either a normal chow diet or a high-fat diet. We found that the increasing dose of d -serine in the drinking water significantly suppressed the intake of high-fat diet, but not the normal chow diet [110]. d -serine water at 1.5 % (weight/volume) concentration also suppressed the intake of a high-sucrose diet and a high-protein diet.…”
Section: Resultsmentioning
confidence: 99%